PENINGKATAN KOMPETENSI GURU TERHADAP PENGGUNAAN METODE BERVARIASI DALAM PROSES PEMBELAJARAN MELALUI IMPLEMENTASI IN HOUSE TRAINING - wati, erna (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2019)
This study aims to describe the process of using varied methods in the learning. This research is a school action research by taking 23 research subject. The research was carried out in two cycles of cycles and each cycle consisted of 4 stages: planning, implementing, observing and reflecting. The esthabilished performance indicators are that if a minimum of 85% of teachers is classified as capable and good in using varied methods in the learning process, then it can be said that the actions implemented are successful. The aspect measured in assessing the success of the action is the teacher?s understanding of the use of varied methods in the learning process and the results of the implementation of In House Training (IHT) activities. The results of the study show, in the first cycle there was an increase in teacher competence in using varied methods in the learning process properly and correctly namely by 57%, while in the second cycle increased sharply to 91%. Therefore it can concluded that through the implementation of in House Training (IHT)_activities can improve teacher competency in using varied methods in the learning process correctly in SD Negeri 1 Pureulak which is marked by the achievement of performance indicators in cycle II. Thust it can be suggested to other schools that the application of In House Traning (IHT) activities can be applied as an alternative in increasing teacher competence in using varied methods in the learning process.